Timing of LGM and deglaciation in the Southern Swiss Alps - Scapozza, Cristian; Castelletti, Claudio; Soma, Linda; Dall’Agnolo, Stephan,; Ambrosi, Christian (Géomorphologie : relief, processus, environnement, 2015)
Detailed mapping of Quaternary formations in Southern Switzerland (Mendrisiotto and neighbouring regions in Italy) and a compilation of radiocarbon dating make it possible to reconstruct the geometry and chronology of the Last Glacial Maximum (LGM) in the Southern Swiss Alps. A detailed chronostratigraphy of the main recessional stadials during the Lateglacial and beginning of the Holocene can also be obtained. The defined glacial stadials were correlated with the NGRIP Greenland isotopic record. An analysis of the calibrated maximum and minimum ages of the LGM allows this episode to be limited to between 28,500 and 22,900 cal BP (24,500–19,000 14C BP). The LGM advance could then tentatively been correlated with the GS-3, between 27,400 and 22,700 cal BP. For the Pleniglacial and the Pleniglacial/Lateglacial transition, the first recessional phases after the LGM were positioned between ca. 22,500 and 21,000 cal BP, and may correspond to the two first cold events of the GS-2c. The first Lateglacial stadial was the Melide stadial, and may match with one of the two cold events at 20,450 or 19,850 cal BP in NGRIP stratigraphy. In the Leventina and Bedretto Valleys (Ticino glacier), five glacial stadials have been proven for the Oldest Dryas (Biasca, Faido, Airolo, Fontana and All’Acqua stadials), two for the Younger Dryas (Maniò and Alpe di Cruina stadials) and one (Val Corno stadial) corresponding to Greenland Holocene event GH-11.2. La cartographie géologique minutieuse des terrains du Quaternaire dans la Suisse méridionale (Mendrisiotto et régions italiennes environnantes) et la compilation de plusieurs datations radiocarbone ont permis de reconstituer la géométrie et la chronologie du Dernier Maximum Glaciaire (DMG/LGM) dans le Sud des Alpes Suisses. Ces résultats ont aussi permis d’obtenir une chronostratigraphie détaillée des principaux stades glaciaires qui ont marqué le Tardiglaciaire et le début de l’Holocène. Les stades glaciaires définis ont été corrélés aux évènements de l’enregistrement isotopique du ...